Rebuilding the Jawoyn Nation: regional agreements, spatial politics and Aboriginal self-determination in Katherine, Northern Territory - Gibson, Chris (1999)
tag=1 data=Rebuilding the Jawoyn Nation: regional agreements, spatial politics and Aboriginal self-determination in Katherine, Northern Territory tag=2 data=Gibson, Chris tag=3 data=Australian Aboriginal Studies tag=5 data=1 tag=6 data=1999 tag=7 data=10-25 tag=8 data=ABORIGINAL LAND CLAIMS tag=9 data=NATIVE TITLE ACT%KIMBERLEYPE YORK%ARNHEM LAND%TORRES STRAITNADA%INUIT%LAND TENURE tag=10 data=Sinc the High Court's 1992 'Mabo' decision, and the passing of the Native Title Act 1993, many indigenous groups in Australia have sought the means by which more holistic approaches to self-determination can be pursued. Sinc the High Court's 1992 'Mabo' decision, and the passing of the Native Title Act 1993, many indigenous groups in Australia have sought the means by which more holistic approaches to self-determination can be pursued.